2 - Media Imperialism Reconsidered – Again: Local, Western and Indian Media Use in Uganda - Hemant Shah, (Africa Media Review, 2008)
This study examines the use of local, Western and Indian media by Ugandan college students in order to reconsider the media imperialism thesis in the context of increasingly complex global flows of media and culture. We surveyed a convenience sample of 193 students at Makerere University in Kampala in June 2003 and asked, among other topics, about their media use patterns, their perception of cultural threats posed by foreign media and their reasons for liking and disliking local and foreign media. We used a combination of closed and open questions. Consistent with previous studies, we discovered that the respondents preferred local media over foreign. But when asked specifically about foreign media, they preferred Western media to Indian media even though they believed Western media posed a more severe cultural threat to Uganda than Indian media. However, the respondents also may have felt some cultural and political proximity to Indian films despite the language barrier. We also found, again consistent with previous research, that respondents were active rather than passive media users. The respondents seemed particularly active when they expressed dislike for media. The respondents also raised concerns about intra-national cultural dominance by the major language group in the country. The results suggest that the media imperialism thesis may be reconsidered again to take into account complexities created by South-to-South media flow, but also intra-national concerns about cultural domination and subordination.